Ánálise da capacidade funcional e da distribuição regional da ventilação pulmonar em pacientes com doença de chagas - Oliveira, Georges Willeneuwe de Sousa (2010)
INTRODUCTION: Cardiac and pulmonary manifestations of the Chagas disease (CD) affect between 20-30% of the infected subjects. The chronic Chagas cardiomyopathy (CCC) has some peculiarities such as arrhythmias and, especially heart failure (HF) and is potentially lethal due to left ventricular dysfunction. How respiratory disorders, patients get progressive loss of functional capacity, which contributes to a poor quality of life related to disease. Measurements of lung volume by the movement of the chest wall surface are an alternative evaluation of lung function and kinematics of complex thoracoabdominal for these patients. OBJECTIVE: evaluate the kinematics of the thoracoabdominal complex through the regional pulmonary volumes and to correlate with functional evaluation of the cardiorrespiratory system in patients with Chagas disease at rest. MATERIALS AND METHODS: a cross-section study with 42 subjects had been divided in 3 groups, 15 composed for patients with CCC, 12 patients with HF of different etiologies and 15 healthful presented control group. An optoelectronic plethysmography (POE), Minnesota questionnaire, six minute walk test, spirometer and manovacuometer was used. RESULTS: It was observed in the 6MWT where group CRL presented greater distance 464,93±44,63m versus Group HF with 399,58± 32,1m (p=0,005) and group CCC 404±68,24m (p=0,015), both the groups presented difference statistics with regard to Group CRL. In the manovacuometer 54,59±19,98; of the group CCC and 42,11±13,52 of group IC found group CRL presented 81,31±15,25 of the predicted versus, presenting in relation to group CRL. In the POE it observed a major contribution in abdominal compartment in patients with IC if compared like CCC and control groups. On the basis of the questionnaire of quality of life of Minessota, verified a low one groups CCC and IC 43,2±15,2 and 44,4±13,1, respectively (p<0,05) when compared with the control group (19,6±17,31). CONCLUSION: it seems that the patients with CCC possess same functional and respiratory characteristics, observed for the POE, 6MWT, manovacuometer and spirometer to the patients of group HF, being able to consider similar interventions for this complementary group as therapeutical of this neglected disease